Exploring the potential of the critical shear crack theory for reinforced and post-tensioned glass beams: Initial analysis and experiments. (15th March 2023) - Cupać, Jagoda; Louter, Christian; Nussbaumer, Alain
Abstract: In the evolution of structural glass beam elements, the requirements for post-fracture load bearing capacity and safe failure behaviour have led to the development of reinforced and post-tensioned beams. Maximum bending capacity in the post-fracture state is normally associated with extensive yielding of the reinforcement, providing a safe failure mechanism through apparent ductility of the composite beam section. This can be achieved as long as the propagation of primary flexural cracks does not compromise the transfer of shear from the load points to the supports. Although shear failure is typically not critical for the ultimate limit state design of 'normal' unreinforced glass beams, it may govern the load-bearing and deformation capacity in the post-fracture state for reinforced and post-tensioned glass beams. This paper presents exploratory experiments and initial analysis of the shear failure phenomenon in the post-fracture state of reinforced and post-tensioned glass beams. Potential shear transfer mechanisms are identified based on the critical shear crack theory developed for reinforced concrete members and applied in the analysis of shear failures observed in four-point bending tests of post-tensioned glass beams. The behaviour of fractured laminated glass under mixed-mode (tension+shear) loading is explored on a limited set of small-scale double-notched glass specimens, demonstrating the feasibility of the applied test methodology. Preliminary findings of the present study may serve as a basis for further investigations of shear resistance of glass beams. Typical shear failure kinematics and suitable constitutive laws of the applied materials need further investigation in order to provide design recommendations for the prediction of shear resistance of reinforced and post-tensioned glass beams. Highlights: Shear failure has been observed in bending tests on post-tensioned glass beams. In the post-fracture state, shear failure may reduce bending capacity of glass beams. Shear transfer mechanisms are identified based on the critical shear crack theory. Fractured laminated glass is explored in double-notched mixed-mode tests.